Biodiversity and composition of methanogenic populations in the rumen of cows fed alfalfa hay or triticale straw. Issue 2 (8th January 2013) - Kong, Yunhong; Xia, Yun; Seviour, Robert; Forster, Robert; McAllister, Tim A.
Abstract It is clear that methanogens are responsible for ruminal methane emissions, but quantitative information about the composition of the methanogenic community in the bovine rumen is still limited. The diversity and composition of rumen methanogens in cows fed either alfalfa hay or triticale straw were examined using a full‐cycle rRNA approach. Quantitative fluorescence in situ hybridization undertaken applying oligonucleotide probes designed here identified five major methanogenic populations or groups in these animals: the Methanobrevibacter TMS group (consisting of Methanobrevibacter thaueri, Methanobrevibacter millerae and Methanobrevibacter smithii), Methanbrevibacter ruminantium‐, Methanosphaera stadtmanae‐, Methanomicrobium mobile‐, and Methanimicrococcus‐related methanogens. The TMS‐ and M. ruminantium‐related methanogens accounted for on average 46% and 41% of the total methanogenic cells in liquid (Liq) and solid (Sol) phases of the rumen contents, respectively. Other prominent methanogens in the Liq and Sol phases included members of M. stadtmanae (15% and 33%), M. mobile (17% and 12%), and Methanimicrococcus (23% and 9%). The relative abundances of these methanogens in the community varied among individual animals and across diets. No clear differences in community composition could be observed with dietary change using cloning techniques. This study extends the known biodiversity levels of the methanogenic communities in the rumen of cows.